2017
DOI: 10.1186/s13293-017-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between cannabis use and methadone maintenance treatment outcomes: an investigation into sex differences

Abstract: BackgroundCannabis will soon become legalized in Canada, and it is currently unclear how this will impact public health. Methadone maintenance treatment (MMT) is the most common pharmacological treatment for opioid use disorder (OUD), and despite its documented effectiveness, a large number of patients respond poorly and experience relapse to illicit opioids. Some studies implicate cannabis use as a risk factor for poor MMT response. Although it is well established that substance-use behaviors differ by sex, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 54 publications
9
50
3
Order By: Relevance
“…During follow up, prevalence of cannabis use during MMT therapy continued to be high though lower than the prevalence during intake. This prevalence is consistent with similar studies done in the rest of the world which have reported a rate of 46.9-61.5% (16,21,22). This is a significant finding since continued use of cannabis during MMT has been associated with negative effects such as high attrition and increased use of illicit substances.…”
Section: Prevalence and Pattern Of Cannabis Usesupporting
confidence: 91%
See 4 more Smart Citations
“…During follow up, prevalence of cannabis use during MMT therapy continued to be high though lower than the prevalence during intake. This prevalence is consistent with similar studies done in the rest of the world which have reported a rate of 46.9-61.5% (16,21,22). This is a significant finding since continued use of cannabis during MMT has been associated with negative effects such as high attrition and increased use of illicit substances.…”
Section: Prevalence and Pattern Of Cannabis Usesupporting
confidence: 91%
“…In addition, prevalence of cannabis use in patients on methadone maintenance treatment is higher than the prevalence in the general population (14). Some studies have reported a high prevalence ranging at 50-70% (15,16). while a study in Finland reported a lower prevalence of 30% (17).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations